2003
DOI: 10.1021/jf034070b
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a Cationic Acrylate Polymer with Caseins:  Biphasic Effect of Eudragit E100 on the Stability of Casein Micelles

Abstract: When whole or skim milk was incubated with the cationic acrylate polymer Eudragit E100, a biphasic effect on the stability of casein micelles was observed. A precipitation phase was observed at low polymer/casein ratios. Strikingly, a solubilization phase of the aggregates was observed when the ratios of polymer/casein were increased. Purified alpha(s)-, beta-, and kappa-caseins or dephosphorylated caseins were equally precipitated and resolubilized by the cationic polymer, indicating no special selectivity fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 24 publications
3
24
1
Order By: Relevance
“…Total protein concentration in human plasma from normal volunteers was evaluated by Biuret or by direct absorbance at 280 nm as previously described 11. The activity of glutamic oxalacetic transaminase (GOT), glutamic pyruvic transaminase (GPT), lactate dehydrogenase (LDH) and alkaline phosphatase (AP) were measured by commercially available enzymatic methods (Wiener Lab., Rosario, Argentina).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Total protein concentration in human plasma from normal volunteers was evaluated by Biuret or by direct absorbance at 280 nm as previously described 11. The activity of glutamic oxalacetic transaminase (GOT), glutamic pyruvic transaminase (GPT), lactate dehydrogenase (LDH) and alkaline phosphatase (AP) were measured by commercially available enzymatic methods (Wiener Lab., Rosario, Argentina).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we described that E100 displays a biphasic coagulating‐resolubilizing effect of caseins and milk fat from bovine milk 11. It was also shown that, from the various intermolecular forces that could be involved in complex formation, both electrostatic and hydrophobic interactions play a critical role between E100 and caseins 11.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It must be emphasized that, in many earlier studies [3][4][5][6][7], much interest has only been focused on the interaction between casein micelles and additives, but no attention has been paid to the interaction between casein monomers (or submicelles) and additives because of the high casein concentration. Here, the ITC results can monitor the interaction of SDS with casein micelles or monomers, respectively.…”
Section: Microcalorimetrymentioning
confidence: 99%
“…However, the form-function relationship is not static in nature. Many studies have shown that solutes and solvents can significantly alter the behavior and overall performance of casein [3][4][5][6][7]. In commercial products such as casein, mixed systems with surfactants are generally employed to obtain better performance for the products.…”
Section: Introductionmentioning
confidence: 99%